2010
DOI: 10.1002/meet.14504701420
|View full text |Cite
|
Sign up to set email alerts
|

Extending the reach of our collective cultural heritage: The IMLS DCC Flickr Feasibility Study

Abstract: The Flickr Feasibility Study investigated the roles and processes required for a digital collection aggregator to facilitate participation of cultural heritage institutions in Web 2.0 communities. The results demonstrate that providing this service for museums, libraries, and archives can be a natural extension of aggregation activities. While the role is complicated by the varying requirements of different kinds of institutions, analysis of user interactions can guide both collection development and building … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Language ISO 639-2 32 , ISO 639-3 33 , Glottocode 34 , AustLang 35 Genre OLAC Discourse Type Vocabulary 36 , OLAC Linguistic Data Type Vocabulary 37 Type Internet Media Types 38 , DCMItype 39 Subject Library of Congress Subject Headings (LCSH) 40 Names VIAF 41 , LC Name Authority File 42 , OLAC Role Vocabulary 43 , MARC Relator 44 Date W3CDTF 45 , EDTF 46 Place Names ISO 3166 47 , Thesaurus of Geographic Names 48 Other Traditional Knowledge Labels 49 Beyond language names, Genre and Type are the metadata fields with data values most commonly drawn from controlled vocabularies (see Table 1). The OLAC metadata scheme prescribes the use of the OLAC Linguistic Type controlled vocabulary to represent the genre in an instance of the Type element.…”
Section: Controlled Vocabulariesmentioning
confidence: 99%
“…Language ISO 639-2 32 , ISO 639-3 33 , Glottocode 34 , AustLang 35 Genre OLAC Discourse Type Vocabulary 36 , OLAC Linguistic Data Type Vocabulary 37 Type Internet Media Types 38 , DCMItype 39 Subject Library of Congress Subject Headings (LCSH) 40 Names VIAF 41 , LC Name Authority File 42 , OLAC Role Vocabulary 43 , MARC Relator 44 Date W3CDTF 45 , EDTF 46 Place Names ISO 3166 47 , Thesaurus of Geographic Names 48 Other Traditional Knowledge Labels 49 Beyond language names, Genre and Type are the metadata fields with data values most commonly drawn from controlled vocabularies (see Table 1). The OLAC metadata scheme prescribes the use of the OLAC Linguistic Type controlled vocabulary to represent the genre in an instance of the Type element.…”
Section: Controlled Vocabulariesmentioning
confidence: 99%
“…Our interactions with the photostream data providers indicated that technical staff for digital projects can be prohibitively expensive for some smaller institutions. More surprisingly, larger institutions also may not have sufficient personnel to prioritize these kinds of new initiatives (Jett et al, 2010). Thus, as rewarding as engagement with Web 2.0 communities can be, many cultural heritage institutions lack the human resources, expertise, and infrastructure needed to get them off the ground or sustain them once developed.…”
Section: Aggregator As Facilitatormentioning
confidence: 99%
“…The DCC team has continued to examine how cultural heritage institutions can take advantage of Flickr to connect with users outside the Commons, where, in fact, there is more freedom to upload photographs for which copyright restrictions may apply. Previously we have reported on the FFS metadata scheme; methods and workflows developed for uploading images; engagement with the library and museum data providers; and user interactions with the collection (Palmer, 2010; Jett et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The project team worked with five contributors to the IMLS DCC aggregation, diverse cultural heritage institutions ranging from large academic archives to small public libraries, to create the IMLS DCC Flickr photostream. The photostream, containing 8 distinct collections with a total of 4,471 images, offered institutions a viable approach to sharing their content outside of the limitations associated with participation in the Commons on Flickr [1]. We have previously reported on the FFS metadata scheme; methods and workflows developed for uploading images; engagement with the library and museum data providers; and user interactions with the collection [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…The photostream, containing 8 distinct collections with a total of 4,471 images, offered institutions a viable approach to sharing their content outside of the limitations associated with participation in the Commons on Flickr [1]. We have previously reported on the FFS metadata scheme; methods and workflows developed for uploading images; engagement with the library and museum data providers; and user interactions with the collection [1], [2]. In this poster we report on a framework to facilitate both the analyses of the accelerating use of the photostream and interactions with contributing institutions to examine trends, benefits, roadblocks, and services for cultural heritage institutions that wish to participate in Web 2.0 sharing.…”
Section: Introductionmentioning
confidence: 99%